Topographic organization of the human and non-human primate subthalamic nucleus - Alkemade, Anneke (Brain Struct Funct, 2015)
Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is used to relieve motor symptoms of Parkinson’s disease. A tripartite system of STN subdivisions serving motoric, associative, and limbic functions was proposed, mainly based on tracing studies, which are limited by low numbers of observations. The evidence is compelling and raises the question as to what extent these functional zones are anatomically segregated. The majority of studies indicate that there is anatomical overlap between STN functional zones. Using ultrahigh-resolution magnetic resonance imaging techniques it is now possible to visualize the STN with high spatial resolution, and it is feasible that in the near future stereotactic guided placement of electrical stimulators aided by high-resolution imaging will allow for more specific stimulation of the STN. The neuroanatomical and functional makeup of these subdivisions and their level of overlap would benefit from clarification before serving as surgical targets. We discuss histological and imaging studies, as well as clinical observations and electrophysiological recordings in DBS patients. These studies provide evidence for a topographical organization within the STN, although it remains unclear to what extent functionally and anatomically distinct subdivisions overlap.